Experience of organizing foster families for elderly citizens in the subjects of the Russian Federation - R. M. Sadykov; N. L. Bolshakova (Вестник университета)
The article discusses a special and effective form of living arrangements for the elderly and disabled in a foster family in the regional entities of the Russian Federation. The experience of organizing a foster or substitute family has been developed in a number of European countries and the USA. It has been established that this technology provides an elderly person with the necessary care and living conditions, leisure activities, psychological support, and additional material support for a foster family. The development of the institution of a foster family for the elderly as an innovative form of their life arrangement will significantly improve the quality of life of older citizens, change their “social well-being”, save them from the problem of loneliness, and strengthen the connection between generations. To solve the problems of the elderly in 2004, the project “Foster families for the elderly and disabled” was launched. The mission of this project is to organize public support, help with household chores and psychological support for lonely people. Most of the regions of the Russian Federation supported the initiative of the project and the subjects have their own experience in implementing the Foster Families for Senior Citizens project. Each subject of the Russian Federation has its own characteristics and differences in the creation of foster families for the elderly, which is associated with the presence of its own legislative framework for the implementation of this project.